Penerokaan ciri-ciri psikometrik skala kesejahteraan psikologi dalam kalangan sampel Malaysia - Mohammad Izzat Akmal Shariff; Wan Shahrazad Wan Sulaiman (Penerbit Universiti Kebangsaan Malaysia, 2018)
In the globalization era which is more challenging, our country needs productive, knowledgeable, competent and competitive work force. The ability to compete in the global market depends on the quality and productivity of employees. Therefore, employees wit physical, mental and psychological well-being are important to ascertain the effectiveness of work in the organization. This study aims to explore the psychometric properties of the Psychological Well-Being Scale. A total of 209 employees from the Prime Minister’s Department participated as respondents in this study. The Psychological Well-Being Scale was used as the research instrument. Results of factor analysis using Principal Component Analysis technique and varimax rotation with scree plot extracted three factors which contributed 39.99 percent variance and produced loadings between .045 to .779. The three factors extracted were Self-Acceptance, Environmental Mastery and Autonomy. Results of reliability also showed moderate and good reliability with alpha Cronbach .920 for Self-Acceptance, .779 for Environmental Mastery and .511 for Autonomy. Findings of this study give implication that the Psychological Well-Being Scale has good psychometric properties and can be used to measure psychological well-being among employees in Malaysia.